SITUS HUNIAN PRASEJARAH DI SARMI [The Prehistoric Settlement Site in Sarmi] - Suroto, Hari (BALAI ARKEOLOGI PAPUA, 2017)
Sarmi is located on the northern coast of Papua. In prehistoric times, Sarmi became the goal of the migration of inland and Austronesian speakers. They live settled and form settlements. Prehistoric archeology research at Sarmi has never been done. The purpose of this study was to identify, find, identify prehistoric settlement sites. The data collection method used is surface survey. The analysis uses artifact analysis, and contextual analysis. In this study managed to find an open settlement site consisting of Edwas Site, Karbos and Fromadi. Human supporters of Edwas Site are hunters and gatherers of forest products, while human supporters of Karbos site and Fromadi site live hunting and gathering, searching for seafood as well as trading activities or exchanging commodities with outsiders. ABSTRAKSarmi terletak di pesisir utara Papua. Pada masa prasejarah, Sarmi menjadi tujuan migrasi penduduk dari pedalaman maupun penutur Austronesia. Mereka hidup menetap dan membentuk pemukiman. Penelitian arkeologi prasejarah di Sarmi belum pernah dilakukan. Tujuan penelitian ini adalah untuk mengetahui, menemukan, mengidentifikasi situs hunian prasejarah. Metode pengumpulan data yang digunakan adalah survei permukaan tanah. Analisis menggunakan analisis artefak, dan analisis kontekstual. Dalam penelitian ini berhasil menemukan situs hunian terbuka yang terdiri atas Situs Edwas, Karbos dan Fromadi. Manusia pendukung Situs Edwas merupakan pemburu dan peramu hasil hutan, sedangkan manusia pendukung Situs Karbos dan Situs Fomadi hidup berburu dan meramu, mencari hasil laut serta beraktivitas perdagangan atau tukar menukar komoditas dengan penduduk luar.